Verification Makhov,s profile for slow positron in Germanium - Sabah Mahmuoud Aman Allah (Tikrit Journal of Pure Science, 2023)
In this paper the mean penetration depths z0 and  Makhov (Implantation) profile I(z,E) were evaluated for low energies positrons(1.5-30/keV)by using a distribution function of  Valkealahti - Nieminen for Germanium for different thicknesses:0.2, 0.4,0.8,1.2,1.4,1.6 μm. The obtained results reveals that the values of  Makhov,s  profile  decreased exponentialy with increasing the positron energy  and profile depths increasing linearly  with increasing  the incident energy. The shape of the Makhov,s  profile reflects the shape of the energy spectrum of the positrons, which  indicates  the annihilation of positrons  inside the material  where  its  wavefunction is delocalized.